Size And Shape Analysis of Female Nose in Malay Ethnic - Rajion, Zainul Ahmad (Faculty of Dental Medicine, Universitas Sumatera Utara, 2009)
Severn! non invasive methods have the results showed that been applied to quantify facial soft tissue morphology. Digital photography is one of the methods that has been used in the assessment of facial profile in different population This study aims to determine nasal soft tissue differences among Malays in Peninsular Malaysia by applying geometric morphometric method with digital photograph. A cross sectional study was carried out on 20 participants from Bugis and Java females with aged range from 2040 years. The photographs were captured using digital SI.R camera (Nikon D80) and analyzed using finite element analysis in MorphoStudiolM software. Seven soft tissue landmarks were digitized on each frontal photograph and six on the lateral one. The study error for both samples was within acceptable limits as there were no statistical differences (p>0.05) in duplicated digitization The results showed that the oomparison of size revealed that Bugis females were smaller in upper and lower nasal region abont 17- 33%. Bugis females shape showed differences in upper and lower nasal area by 20%. In lateral profile there was a decreased size in lower nasal area in Bugis females by 17- 33% and the difference in shape by 20%. The nasal region was significantly smaller in size and more different in shape for Bugis females than Javanese females. Computer aided photogrammetric analysis has the ability to depict and quantify local shape and size changes of nasal soft tissue differences between Java Malay and Bugis female groups.